2006
DOI: 10.1016/j.jnutbio.2005.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Biotin supplementation decreases the expression of the SERCA3 gene (ATP2A3) in Jurkat cells, thus, triggering unfolded protein response

Abstract: Protein folding in the endoplasmic reticulum (ER) depends on Ca 2+ ; uptake of Ca 2+ into the ER is mediated by SERCA3. The 5′-flanking region of the SERCA3 gene (ATP2A3) contains numerous binding sites for the transcription factors Sp1 and Sp3. Biotin affects the nuclear abundance of Sp1 and Sp3, which may act as transcriptional activators or repressors. Here we determined whether biotin affects the expression of the SERCA3 gene and, thus, protein folding in human lymphoid cells. Jurkat cells were cultured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
1
9
0
1
Order By: Relevance
“…Nitric oxide (NO) is a fundamental signaling molecule involved in several physiological processes including host defense, and the regulation of vascular tone as well as a potent cytotoxic effector involved in human diseases pathogenesis (62), Griffin et al showed that decreased ATP2A3 expression induces unfolded protein response (UPR) in Jurkat cells (65) and our sequencing results also observed that down-regulation of ATP2A3 resulted in induction of unfolded protein response in these cells. Recently, researchers showed decreased PDE2A expression leads to increased accumulation of cAMP and myocardial contractility after beta-adrenogenic receptor stimulation (66, 67).…”
Section: Discussionsupporting
confidence: 52%
“…Nitric oxide (NO) is a fundamental signaling molecule involved in several physiological processes including host defense, and the regulation of vascular tone as well as a potent cytotoxic effector involved in human diseases pathogenesis (62), Griffin et al showed that decreased ATP2A3 expression induces unfolded protein response (UPR) in Jurkat cells (65) and our sequencing results also observed that down-regulation of ATP2A3 resulted in induction of unfolded protein response in these cells. Recently, researchers showed decreased PDE2A expression leads to increased accumulation of cAMP and myocardial contractility after beta-adrenogenic receptor stimulation (66, 67).…”
Section: Discussionsupporting
confidence: 52%
“…Given that Sp3 may act as transcriptional repressor, it has been proposed that effects of biotin on SERCA3 expression are mediated by the increased nuclear abundance of Sp3 in biotin-supplemented cells (58). Decreased expression of SERCA3 reduces the sequestration of calcium in the endoplasmic reticulum (ER) (83).…”
Section: Sp1 and Sp3mentioning
confidence: 99%
“…We speculate that one or more of the many biotin-dependent transcription factors participate in the regulation of the two genes (5, 9, 21). In addition, we propose that decreased expression of the sarcoplasmic/endoplasmic reticulum ATPase 3 (SERCA3) in biotin-supplemented cells decreases the transport of Ca 2+ from the cytoplasm into the endoplasmic reticulum, leading to increased concentrations of Ca 2+ in the cytoplasm (20). Cytoplasmic free Ca 2+ is known to enhance the production of NO in Jurkat cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Second, biotin deficiency causes nuclear translocation of the transcription factor NF-κB, mediating transcriptional activation of anti-apoptotic genes (9). Third, biotin supplementation decreases expression of the SERCA3 gene, thereby enhancing the levels of Ca 2+ in the cytoplasm and triggering the unfolded protein response (20). Fourth, biotin deficiency activates jun/fos signaling, activating AP1-dependent pathways (5).…”
mentioning
confidence: 99%